Rehabilitation after a complete avulsion of the proximal rectus femoris muscle: Considerations from a case report - Baumgart, Christian; Grim, Casper; Heiß, Rafael; Ehrenstein, Philipp; Freiwald, Jürgen; Hoppe, Matthias Wilhelm (International Journal of Environmental Research and Public Health, 2021)
Background: A complete avulsion of the proximal rectus femoris muscle is a rare but se-verity injury. There is a lack of substantial information for its operative treatment and rehabilitation; in particular there is a lack of biomechanical data to evaluate long-term outcomes. Case presenta-tion: The case report presents the injury mechanism and surgical treatment of a complete avulsion of the proximal rectus femoris muscle in a 41-year-old recreational endurance athlete. Moreover, within a one-year follow-up period, different biomechanical tests were performed to get more functional insights into changes in neuromuscular control, structural muscle characteristics, and endurance performance. Within the first month post-surgery, an almost total neuromuscular inhibition of the rectus femoris muscle was present. A stepwise reduction in inter-limb compensations was ob-servable (e.g., in crank torque during cycling) during the rehabilitation. Muscular intra-limb compensations were shown at six months post-surgery and even one year after surgery, which were also represented in the long-term adaption of the muscle characteristics and leg volumes. A changed motor control strategy was shown by asymmetric muscle activation patterns during ergometer cy-cling, while the power output was almost symmetric. During rehabilitation, there might be a benefit to normalizing neuromuscular muscle activation in ergometer cycling using higher loads. Conclu-sions: While the endurance performance recovered after six months, asymmetries in neuromuscular control and structural muscle characteristics indicate the long-term presence of inter-and intra-limb compensation strategies.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Electromyography; Isokinetic; Muscle injury; Quadriceps; Rehabilitation; Strength; Surgery; Tendon rupture